Ultrasonic guided waves for monitoring corrosion of FRP wrapped concrete structures - Sharma, A.; Sharma, S.; Sharma, S.; Mukherjee, Abhijit (Elsevier Ltd, 2015)
Reinforced concrete (RC) structures affected by corrosion of steel bars are often repaired and rehabilitated by wrapping fibre reinforced polymer (FRP) sheets. Most commonly available FRP materials are glass and carbon fibre composites. This paper uses ultrasonic guided waves as a non-destructive tool to monitor the initiation and progression of corrosion in reinforcing bars in concrete after repairing with bonded FRP sheets. Concrete cylinders embedded with reinforcing bars are subjected to accelerated impressed current corrosion in chloride environment. After specific days of exposure to corrosive environment the cylinders are repaired by wrapping with GFRP and CFRP sheets. Anodic current was further continued for specified times. Specific core and surface seeking guided wave modes were used to ultrasonically measure the resistance offered by FRP wraps to corrosion. The ultrasonic measurements were correlated with destructive parameters of pull-out strength and mass loss. This paper demonstrates that guided waves were able to discern the corrosion protection offered by the FRP. It is observed that Glass FRP gives better protection than Carbon FRP.